Human Jurisprudence Public Law as Political Science - Schubert, Glendon (University of Hawai'i Press, 1975)
This book provides a rare view of a creative scholar at work during a highly productive phase of his career. It shows him as an innovator, theorist, methodologist, "missionary," critic, and scientist, but he remains, withal, in his fashion, a humanist. He believes that institutions and processes-particularly law, politics, and scholarship-are best understood in human terms. With Holmes, he believes that law is a prediction of what courts will do; hence, to understand law it is necessary to understand judicial behavior. A full explanation of a judge's behavior would take into account his health (both physical and mental), his personality, his culture and society, and his ideology. Glendon Schubert concedes this but focuses primarily on ideology because he believes the other variables are sublimated in it. Therefore, to him, ideology-attitudes toward human values-is the basic explanation of judicial behavior, and jurisprudence is necessarily human. The studies in this volume are important in the study of judicial behavior, for they broke new ground, and some were forerunners of major books, such as The Judicial Mind, which was published in 1965. Each shows Professor Schubert's concern at the time they were written, and taken together they show the movement and growth of his ideas and interests.